Building the future: innovative application and development prospect of telecommunication big data open platform in for intelligent social governance - QIU Baohua (Dianxin kexue)
The importance of big data in telecommunications for the governance of intelligent societies was delved into. Taking into account the current policy environment, the research objectives and contributions was elucidated. The theoretical foundations of telecommunications big data, its developmental trends, and its status both domestically and internationally was presented, and the necessity and application directions for constructing a big data open platform was discussed. The solutions to key issues, including multi-domain data fusion, spatiotemporal data model construction, and big data openness strategies, was deeply analyzed, and the project outcomes and their impact at the technological, economic, and social levels was forecasted. This study provides a valuable reference for the future application of telecom big data.